Bump ahead - Mr. Big; Elson, Kevin; Atlantic Recording Corporation (New York : Atlantic Recording Corporation, 1993)
Contains eleven tracks of hard rock genre.
CD 1: Colorado Bulldog / (4:14) -- Price You Gotta Pay / (3:55) -- Promise Her The Moon / (4:07) -- What's It Gonna Be / (3:54) -- Wild World / (3:27) -- Mr. Gone / (4:35) -- The Whole World's Gonna Know / (3:53) -- Nothing But Love / (3:58) -- Temperamental / (4:55) -- Ain't Seen Love Like That / (3:31) -- Mr. Big / (4:16).
Koleksi Khas Wiramanja.
Eric Martin (voice), Billy Sheehan (bass), Pat Torpey (drums), Paul Gilbert (guitar).
Title from disc label.
Keywords: Songs, English; Rock music